How mobility and other UArctic-programs can be used to communicate new knowledge. - Johnson, Mona (Arctic Portal, 2011)
Mona Johnson, Finnmark University College, talks here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. Please click on the link above to see the video.